FRI0537 Automated Joint Space Width Measurement and Digital X-Ray Radiogrammetry in Early RA. (15th July 2016) - Platten, M.; Kisten, Y.; Kälvesten, J.; Arnaud, L.; Forslind, K.; van Vollenhoven, R.
Abstract : Background: Despite technological advancements and the availability of ultrasound and magnetic resonance imaging modalities, conventional radiography still remains the main imaging tool in Rheumatoid Arthritis (RA) patient management (1). One of the validated methods of radiographic scoring in RA, the modified Sharp van der Heijde (SHS) method, has much strength but is time-consuming, observer-dependent, and requires training, and is therefore seldom used in clinical practice (1, 2). Automated digital methods have been developed for analysing radiographs and may provide useful information on Joint Space Width (JSW) and/or Bone Mineral Density (BMD). Objectives: To assess the feasibility and correspondence of fully automated digital measurements of JSW with conventional methods in early RA. Methods: Patient characteristics and radiographic reports scored by the SHS method of 119 early RA patients were acquired from the SWEFOT database. From this cohort, 96 patients had both baseline and follow-up JSW and BMD measurements. Fully automated bilateral BMD of metacarpal diaphyses 2–4 and JSW of MCP joints 2, 3 & 4 (Sectra, Linköping, Sweden) were assessed. Additionally, JSW was compared to the joint space narrowing (JSN) score. Multilevel mixed models taking into account correlations between joints of the same hand, contralateral hand and repeated visits were used. Furthermore, these models were adjusted for height, age, gender and BMI. Results: We studied 119 early RA patients (78% female), with an average age of 54 ±14.4 years. In 576 joints, patients with both baseline and follow-up JSW and BMD measurements, a significant reduction from baseline to 1 year was shown in the mean JSW (0.169 ±0.019cm to 0.166 ±0.019cm, p<0.01) and mean BMD (0.583 ±0.068g/cm 2 to 0.566 ±0.074g/cm 2, p<0.01). Significant correlations between JSW and BMD were observed at baseline (r=0.32, p<0.01) and 12-months (r=0.35, p<0.01). Inverse correlations emerged between automated JSW and SHS Joint Space Narrowing (JSN) assessments at baseline (r=-0.29, p<0.01) and 12-months (r=-0.24, p=0.014). JSWs of undamaged (JSN=0) joints were wider than damaged joints (0.168cm [95% CI: 0.170–167] versus 0.154cm [95% CI: 0.163–0.146]). Similarly the unadjusted multilevel model showed significant differences in JSW between undamaged (0.168cm [95% CI: 0.172–0.164]) and damaged joints (0.163cm [95% CI: 0.168–0.158cm]), p<0.01. This difference remained significant in the adjusted model (0.166cm [95% CI: 0.170–0.161] versus 0.162cm [95% CI: 0.168–0.156], p<0.05). Conclusions: Digital JSW may have potential as a quick and observer-independent measure of cartilage damage in early RA. References: Boini S, Guillemin F. Radiographic scoring methods as outcome measures in rheumatoid arthritis: properties and advantages. Annals of the rheumatic diseases. 2001;60(9):817–27. Peloschek P, Langs G, Weber M, Sailer J, Reisegger M, Imhof H, et al. An automatic model-based system for joint space measurements on hand radiographs: initial experience. Radiology. 2007;245(3):855–62. Disclosure of Interest: M. Platten: None declared, Y. Kisten: None declared, J. Kälvesten Employee of: Sectra AB, L. Arnaud: None declared, K. Forslind: None declared, R. van Vollenhoven: None declared